Sistem Pengukuran Modulus Elastisitas Beton Menggunakan Metode Ultrasonic Pulse Velocity - Amanda Purwanto; Abdul Ro’uf (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
Modulus of elasticity of concrete usually measured by Destructive Testing which is not considered as an effective way, because It will destroy the concrete. Ultrasonic Pulse Velocity can be a solution to measure value of modulus of elasticity without destructing it. The concept of the system is to look for velocity of wave, then put the value into modulus elasticity formula.UPV system will transmit ultrasonic wave through concrete. HC-SR04 used for generating 40 kHz wave, increasing voltage of wave on receiver, and calculating time travel. The voltage of wave sent by HC-SR04 is only about 10 volt, so that power and voltage of wave has to be amplified. Piezoelectric is used as a transducer which can converts electrical to mechanical energy. The results of this research shows that error value on wave velocity measurement have an average value for about 18,2% compared to result of UPV Pundit. Static modulus of elasticity from compressive test is compared to value of dynamic modulus of elasticity that is obtained by UPV system with HC-SR04. Ratio between two values is about 45% - 249%.